Hedging Brevity Risk with Mortality-based Securities - Richard MacMinn; Andreas Richter (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
In 2003, Swiss Re introduced a mortality-based security designed to hedge excessive mortality changes for its life book of business. The concern was apparently brevity risk, i.e., the risk of premature death. The brevity risk due to a pandemic is similar to the property risk associated with catastrophic events such as earthquakes and hurricanes and the security used to hedge the risk is similar to a CAT bond. This work looks at the incentives associated with insurance-linked securities. It considers the trade-offs an insurer or reinsurer faces in selecting a hedging strategy. We compare index and indemnity-based hedging as alternative design choices and ask which is capable of creating the greater value for shareholders. Additionally, we model an insurer or reinsurer that is subject to insolvency risk, which creates an incentive problem known as the judgment proof problem. The corporate manager is assumed to act in the interests of shareholders and so the judgment proof problem yields a conflict of interest between shareholders and other stakeholders. Given the fact that hedging may improve the situation, the analysis addresses what type of hedging tool would be best to use. We show that an indemnity-based security tends to worsen the situation, as it introduces an additional incentive problem. Index-based hedging, on the other hand, under certain conditions turns out to be beneficial and therefore clearly dominates indemnity-based strategies. This result is further supported by showing that for the same strike prices the current shareholder value is greater with the index-based security than the indemnity-based security.
urn:nbn:de:bvb:19-epub-1219-6
Keywords: G22; G32; D82; 650; alternative risk transfer; insurance; default risk